2020
DOI: 10.1016/j.jare.2020.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of elements with fractional-order impedance based on homogenous distributed resistive-capacitive structures and genetic algorithm

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…GAs introduced by Holland [49] , is a stochastic, effective, and broadly used evolutionary computation algorithm developed to solve real-valued numerical optimization problems [49] . GAs is easy implemented, robust, simple, efficient and reliable global search algorithm that uses three basic operators, like crossover, mutation and selection for generating new efficient population with better fitness [50] . The individuals with better fitness are less likely to trap in local minima.…”
Section: Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…GAs introduced by Holland [49] , is a stochastic, effective, and broadly used evolutionary computation algorithm developed to solve real-valued numerical optimization problems [49] . GAs is easy implemented, robust, simple, efficient and reliable global search algorithm that uses three basic operators, like crossover, mutation and selection for generating new efficient population with better fitness [50] . The individuals with better fitness are less likely to trap in local minima.…”
Section: Design Methodologymentioning
confidence: 99%
“…The individuals with better fitness are less likely to trap in local minima. Few recent applications of GAs include electrical circuits [50] , supply chain [51] , lungs cancer [52] and wind speed prediction [53] .…”
Section: Design Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent development indicated that these elements can be designed in the form of solid-state devices based on various approaches, e.g. electrochemical materials [30], [31], electrolytes [32], polymer composites [33], [34], layers of resistive, dielectric and insulating materials [35]. However, these devices are not easily accessible, for instance in a form of standard passive elements series (R, C, L).…”
Section: Fractional-order Immittances and Their Approximationmentioning
confidence: 99%
“…Fractional-order calculus has been confirmed to be an effective instrument for many practical scientific engineering models (Valian et al, 2021; Zhou, 2016). In real problems, fractional differential equations are superior to traditional integer-order equations in describing all kinds of materials with memory properties (Jahanshahi et al, 2021), genetic (Ushakov et al, 2020), and simulating dynamic processes (such as fractal media). The anomalous transport process model in the form of time-fractional (Zhou and Guo, 2018) or space-fractional diffusion equation (She et al, 2021) has attracted researchers’ attention.…”
Section: Introductionmentioning
confidence: 99%